2010
DOI: 10.1007/s12665-010-0582-7
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the effects of longwall mine-induced subsidence on vineyards

Abstract: This paper reports on the design and implementation of a program to monitor the surface effects of longwall mining-induced subsidence on wine grape yields within vineyards of Australia's Hunter Valley. Implemented in 2003, this five-year project incorporated a multiscale, multi-temporal, sliding window monitoring design synchronised with progression of longwall panels. On the vineyard-block scale, individual vine panels were sampled for grape yield. On the regional scale measures of vine photosynthetically act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…However, data obtained from both the vineyards and the individual blocks failed to demonstrate any conspicuous or systematic viticultural impacts caused by mining activities in the studied location over the project's duration. Instead, observed patterns in grape yields were better accounted for by the vine's biological responses to climatic conditions 17 .…”
Section: Thompson Et Almentioning
confidence: 99%
“…However, data obtained from both the vineyards and the individual blocks failed to demonstrate any conspicuous or systematic viticultural impacts caused by mining activities in the studied location over the project's duration. Instead, observed patterns in grape yields were better accounted for by the vine's biological responses to climatic conditions 17 .…”
Section: Thompson Et Almentioning
confidence: 99%
“…The correction of undesirable turns and curves in paddocks imposes additional costs in machinery use and management. In contrast, changes in drainage patterns due to subsidence may be negligible under different cropping and irrigation systems; for instance, Thompson et al , () found no obvious effects of subsidence on vineyard yields, most likely because of the presence of slopes that enabled drainage.…”
Section: Impacts Of Subsidence On Agricultural Landsmentioning
confidence: 99%
“…In some cases, studies in the same region have found conflicting results, and thus it is difficult to get a sense of which impacts are large or small. Post‐mine subsidence severity, geology, soil type and hydrology and the success of mitigation efforts are site‐specific (Booth et al , ; Darmody, ; Hinchliffe, ; Thompson et al , ). Furthermore, it is difficult to conclude whether the magnitude of these impacts on agricultural productivity is small or large as our review found studies from only three regions in the world included field trials: Queensland, Australia (Hinchliffe, ), Illinois Basin, USA (Darmody, ) and North East China (Hu et al , ).…”
Section: Interpretation Of the Literature In The Australian Farming Cmentioning
confidence: 99%
“…Comparatively, land subsidence seems to be one of the most prominent problems in China, because more than 90 % of the coal comes from underground mining, with thousands of underground long-wall panels . The consequence of underground mining with long-wall panels on land includes: (1) hydrological change, soil moisture content increase and water ponding (Darmody et al 1992;Hinchliffe 2003;Hu et al 1997); (2) increased hydraulic conductivity or biphasic flow through soil (Thompson et al 2010); (3) altered groundwater levels and quality (Booth 2006); (4) soil chemical, physical and biological change, and compaction (Hinchliffe 2003;Hu et al 1997); (5) erosion (Hu et al 1997); and (6) topographic change and altered slope (Hinchliffe 2003). Thus, thousands of hectares of subsided land lose productivity.…”
Section: Introductionmentioning
confidence: 99%